An analysis of the academic personnel practices of De Ocampo Memorial Schools - Guiuan, Pia S. (Acampado) ([Quezon City s.n.], 1974)
Criteria from the Magna Carta for Public School Teachers indicate that personnel policies are not clear-cut and suffer from the following defects and weaknesses: recruitment practices do not consider the nature of the work to be performed nor the qualifications needed for it; no definite programs to stimulate professional performance, and communication gap in the interpretation of the educational philosophy and values due to substandard qualifications and professional stagnation of school administrators and the governing body.
Thesis (M.Ed.)--University of the Philippines.
Keywords: De Ocampo Memorial Schools; School personnel management